Peran Roh Kudus dalam Kehidupan Orang Percaya Melalui Cara Hidup Yang Kudus Berdasarkan 1 Petrus 1:13-16 - Grace Melisa; Martina Novalina; Anwar Three Millenium Waruwu; Eddy Simanjuntak (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
This article delves into the pivotal role of the Holy Spirit in guiding believers towards a sanctified life, mirroring that of Jesus. Anchored in the teachings of Peter outlined in 1 Peter 1:13-16, this research aims to bridge the scientific gap regarding the role of the Holy Spirit. Employing a qualitative descriptive approach, the study leverages Biblical texts and literature reviews. The analysis reveals that the Holy Spirit enables life transformation, allowing alignment with God's will and bringing Him glory. The fullness of the Holy Spirit, both temporally and permanently, engenders a profound understanding of God's intentions. Furthermore, the Holy Spirit is the personification of God, leading and guiding in daily life. By liberating the human spirit from sin, the Holy Spirit shapes and steers the lives of believers, enabling them to bear witness to God's will in this world.